Formation of Pedagogical Technical Schools in the Structure of Higher Professional Education of Ukraine in 1920-s: to the History of the Question - Natalia Vitraniuk (Pedagogical Discourse, 2013)
This article analyzes the works of the modern domestic scientists on the problems of formation and development of technical schools as a form of offering of higher professional education in Ukraine in 1920-s. It is found out that in the mentioned period of time fundamental changes in higher education, connected with the national rise, took place. Different interpretations of this question, diversity and discrepancy of thoughts, insufficiency of study of this question have been determined. More detailed analysis showed that the questions, connected with the peculiarities of educational process organization and content of education in pedagogical schools demand profound studies.